2012
DOI: 10.1021/ja301898h
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Principles Directing Charge Transport in Low-Band-Gap Dithienosilole–Benzothiadiazole Copolymers

Abstract: Given the fundamental differences in carrier generation and device operation in organic thin-film transistors (OTFTs) and organic photovoltaic (OPV) devices, the material design principles to apply may be expected to differ. In this respect, designing organic semiconductors that perform effectively in multiple device configurations remains a challenge. Following "donor-acceptor" principles, we designed and synthesized an analogous series of solution-processable π-conjugated polymers that combine the electron-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
94
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 84 publications
7
94
2
Order By: Relevance
“…The polymer exhibits an even more remarkable hole mobility of 9.0 cm 2¨V´1¨s´1 when using a high-k P(VDF-TrFE) ferroelectric polymer as a gate dielectric. These mobility values are significantly larger than those reported previously for its non-fluorinated equivalent (3ˆ10´3 cm 2¨V´1¨s´1 ) [77]. Such a pronounced effect of fluorination may be attributed to the higher backbone planarity, which allows stronger π-stacking in solid state.…”
Section: Charge Transport Properties In Fluorinated Polymerscontrasting
confidence: 61%
See 1 more Smart Citation
“…The polymer exhibits an even more remarkable hole mobility of 9.0 cm 2¨V´1¨s´1 when using a high-k P(VDF-TrFE) ferroelectric polymer as a gate dielectric. These mobility values are significantly larger than those reported previously for its non-fluorinated equivalent (3ˆ10´3 cm 2¨V´1¨s´1 ) [77]. Such a pronounced effect of fluorination may be attributed to the higher backbone planarity, which allows stronger π-stacking in solid state.…”
Section: Charge Transport Properties In Fluorinated Polymerscontrasting
confidence: 61%
“…As photovoltaic devices require high charge carrier mobilities in the out-of-plane direction, SCLC (Space Charge Limited Current) devices have been frequently used to probe the charge carrier mobility in photovoltaic materials. Peng et al [77] reported a SCLC study on two equivalent isoindigo polymers, the PBDTT-ID and the fluorinated PBDTT-FID derivative (see Figure 13). Fluorination resulted in a vertical mobility enhancement by a factor of five (from 6.5 × 10 −4 to 3.2 × 10 −3 cm 2 ·V −1 ·s −1 ) and in a significant increase in Jsc and Voc (see Entry 1, Table 5).…”
Section: Charge Transport Properties In Fluorinated Polymersmentioning
confidence: 99%
“…The short wavelength shifts within each series may be attributed to the weakened D-A interaction resulting from the insertion of thiophene(s); consequently the donor part dominates. Reynold and co-workers 67 reported a similar series of copolymers using the fused ring donor dithieno[3,2-b:2′,3′-d]silole (DTS) in place of CPDT, but the order of λ max was not in accordance with the increasing donor ratio in the backbone as is observed for the CPDT-BT-CPDT series. The DTS-BT-DTS series showed absorptions that were more blueshifted than members of the CPDT-BT-CPDT series that had the same connecting units because the smaller electronegativity of silicon compared with carbon (Si = 1.9oC = 2.5) and the reduced π-electron bond-forming ability of the Si atom makes DTS a stronger donor than CPDT.…”
Section: Resultsmentioning
confidence: 96%
“…Contradictorily, the DTS-BT-DTS copolymer connected with a bithiophene unit showed a longer λ max , at 617 nm, than the copolymer connected with one thiophene unit (λ max = 602 nm); this is a specific phenomenon induced by DTS. 67 Polymer films were prepared by drop casting chloroform solutions of the desired polymer onto glass substrates, and the λ max values Table 2 Optical and electrochemical properties of polymers Abbreviations: E g-opt, optical band gap; Ox, oxidation; Rd, reduction; Δλ, shift between film and solution. recorded in the ultraviolet-visible spectra of the films were compared with those obtained in solution (Table 2 and Supplementary Figure S19 in Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…D-A copolymers have revolutionized the field of organic electronics by showing single-junction solar cells reaching close to 10% power conversion efficiency 17 , carrier mobility 410 cm 2 V À 1 s À 1 in field effect transistors 18 and bipolar transport 19 . The most important feature of D-A copolymers is the possibility of finely tuning the energy bandgap via the selection of the two moieties 20 .…”
mentioning
confidence: 99%